PERDAGANGAN INTERNASIONAL DALAM KRISIS KESEHATAN: TANTANGAN, RESPONS ANGGOTA WTO DAN PROSPEK PENGUATAN SISTEM PERDAGANGAN MULTILATERAL - Silaban, Devi Widyasari; sembiring, fachrudin (Fakultas Hukum Universitas Katolik Indonesia Atma Jaya, 2023)
Trade is a sustainable process that occurs regularly. If sudden health issues emerge, such as Covid-19, it will affect the trade of goods supply chain, but never postpone entirely. WTO members responsively and temporarily impose measures that somehow barriers trade. As time goes by, unilateral measures can be taken regarding members' obligation to open market access as a core principle within WTO. This paper will discuss how members comply with their obligation during Covid-19 by imposing measures; and how unilateral measures can reinforce the multilateral trading system and create trade liberation later. This paper will be written according to normative-juridical methods with a historical approach as the main idea of the analysis process. This paper will accommodate conceptual ideas upon Rules and re-forecasting phenomenon in further economic scale to maintaining ongoing trade. Afterward, members may respond appropriately to health issues relating to the goods supply chain by imposing measures that can be acknowledged to members collectively.